Analysis of the shift in the superconducting transition under pressure in the Anderson-Hubbard two-orbital model - Kosov, A. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The two-orbital Hubbard model is used to obtain formulas for the fermion excitation spectrum in the energy bands hybridized by Anderson \’s interaction. A transition to the Hubbard operators, which diagonalizes the one-site part of the Hamiltonian, allows us to use the Green \’s temperature function technique to take into account the interstitial jump term while studying the superconducting properties of the model. An analysis of the lower part of the energy spectrum leads to a formula for the superconducting transition temperature Tc associated with the pairing of quasiparticles in one of the correlated bands. The dependence of Tc on electron concentration and energy parameters determining the intraatomic correlation is studied. Proposing a simple relation between the value of pressure (P) and width of the correlated band, the dependence of Tc on the pressure was defined. Good agreement between the theoretical calculation of the dependence of Tc on the pressure and the experimental results for Y1-xPrxBa2Cu3O7-delta is found. Comparison of the theoretical and experimental results for the dependence of Tc and its derivative d(lnTc)/dP on Sr and Bi-content (x) in La2-xSrxCuO4 has been made. It is concluded that the model under consideration can be used for the description of the shift in Tc under pressure for a number of superconductors.